Longitudinal bidirectional relationship between children's appetite and diet quality: A prospective cohort study. (1st February 2022) - da Costa, Marta Pinto; Severo, Milton; Oliveira, Andreia; Lopes, Carla; Hetherington, Marion; Vilela, Sofia
Abstract: This study explored the relationship between eating behaviours and diet quality, from 7 to 10y. The sample included 3879 children evaluated, from the Portuguese birth cohort Generation XXI, with complete information on Food Frequency Questionnaire (FFQ) and the Children Eating Behaviour Questionnaire (CEBQ). A healthy eating index (HEI) (range: 9–31) was developed to evaluate the child's diet quality. The eight CEBQ's eating behaviours were included in the analysis. Generalised linear models were used to estimate the associations. Adjusted structural equation modelling was performed to study the direction of the associations. Eating behaviours measured at age 7y tracked to age 10y. A bidirectional inverse association between the food fussiness trait and diet quality was found, with a similar magnitude (p < 0.001), thus a higher score on food fussiness predicted a lower quality of the diet. A higher HEI score at 7y was associated with lower satiety responsiveness at 10y (βstandardized = −0.039), and a higher HEI score at age 10y was associated with higher enjoyment of food at 7y (βstandardized = 0.046). Eating behaviours were linked to diet quality in children with high enjoyment of food and low food fussiness at age 7y linked to a high-quality diet at 10y. In addition, children with high-quality diets at 7y were more likely to have lower food fussiness and satiety responsiveness at 10y. Given the stability of eating behaviours and the bidirectional nature of effects between eating behaviours and dietary quality in the long term, tailored interventions may be needed to encourage the acquisition of healthy eating behaviours and habits in early life.